Primary pulmonary choricarcinoma - Snoj, Žiga (Radiology and oncology (Ljubljana), 2017)
The aim of the study was to establish whether there are different clinical entities of primary pulmonary choriocarcinoma (PPC) that deserve different diagnostic approach and the most optimal treatment. Patients and methods. A systematic review with PubMed search was conducted to identify studies that reported cases of PPC. The eligibility criteria were histological diagnosis of pulmonary choriocarcinoma and thorough examination of the reproductive organs to exclude potential primary choriocarcinoma in the gonads. Furthermore, to illustrate the review we additionally present a patient referred at our institution. Results. 55 cases (17 men) were included in the review with a median age of 34 years. Women with the history of gestational event showed better survival outcome than women without the history of gestational event. Patients treated with combined modality treatment (surgery and chemotherapy) survived longer than the patients without combined modality treatment. Furthermore, multivariate analysis of prognostic factors showed that the combined modality treatment had independent prognostic significance. Size of the tumour showed significant prognostic influence in univariate and multivariate analysis. Conclusions. PPC is an extreme rarity with variable clinical characteristics and outcome. It is important to capture and treat patients in the early stages of the disease. Women with the history of gestational event may show better survival, therefore genetic examination could help us to predict patient%s prognosis. Surgery followed by adjuvant chemotherapy appears to represent the best treatment for PPC.
Keywords: choriocarcinoma; gestational event; horiokarcinom; human pregnancy; nosečnost; primarni horiokarcinom; primary horiokarcinom; pulmonary tumor; rak pljuč